2018
DOI: 10.1080/17518423.2018.1462269
|View full text |Cite
|
Sign up to set email alerts
|

A consecutive case series analysis of a behavioral intervention for enuresis in children with developmental disabilities

Abstract: Children with developmental disabilities (DD) are more likely than typically developing peers to have issues with enuresis. Past research has shown the success of behavioral treatments consisting of scheduled sits and reinforcement for continent voids. However, this research has included small sample sizes, while studies with larger numbers have lacked key information (i.e., baseline rates and follow-up data to evaluate maintenance and generalization). The current study conducted a consecutive case series anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…As will be shown in the current tutorial, datasets with as few as 25 participants or 25 sessions may produce meaningful results using machine learning. With the growing use of consecutive case series designs in behavior analysis (e.g., Hagopian, 2020;Jessel, et al 2019;Lomas Mevers et al, 2018;Rooker et al, 2013), several researchers and practitioners may already have sufficiently large datasets to apply such algorithms. In the following sections, we present a step-by-step application of machine learning using data from a behavioral study published by Turgeon et al (2020).…”
Section: Machine Learning Procedures and Algorithmsmentioning
confidence: 99%
“…As will be shown in the current tutorial, datasets with as few as 25 participants or 25 sessions may produce meaningful results using machine learning. With the growing use of consecutive case series designs in behavior analysis (e.g., Hagopian, 2020;Jessel, et al 2019;Lomas Mevers et al, 2018;Rooker et al, 2013), several researchers and practitioners may already have sufficiently large datasets to apply such algorithms. In the following sections, we present a step-by-step application of machine learning using data from a behavioral study published by Turgeon et al (2020).…”
Section: Machine Learning Procedures and Algorithmsmentioning
confidence: 99%
“…The correspondence measure alone does not indicate how often the individual is requesting to use the restroom; however, this measure in conjunction with rate and percentage of appropriate urinations that were self-initiated provides further information on how often self-initiations are occurring as well as the percentage of opportunities that appropriate urinations are selfinitiated versus prompted. These results are tentative because other studies that have not provided differential consequences for self-initiation correspondence (e.g., Greer et al, 2016;LeBlanc et al, 2005;Lomas Mevers et al, 2018) have also shown improvements in rate, percentage of successes that were self-initiated, and number of voids that were self-initiated, respectively. However, as these studies have not included a selfinitiation correspondence measure, it is unclear the extent to which self-initiations were occurring in the presence or absence of appropriate urinations.…”
Section: Discussionmentioning
confidence: 58%
“…Some toilet training studies have reported the occurrence of BMs across phases of the intervention (Perez al., 2020;Rinald & Mirenda, 2012) or included a follow-up survey with questions about BM continence (Lomas Mevers et al, 2018). However, with only these relatively coarse measures, it remains unclear how the likelihood of appropriate BMs might be affected by improvements in urinary continence.…”
mentioning
confidence: 99%
“…Within the framework of ABA, Azrin and Foxx (1971) developed the seminal approach of toilet training procedures for individuals with intellectual disabilities in a residential facility. Toilet training procedures have continued to evolve over the years, including a broad range of components to consider when developing a protocol (e.g., LeBlanc et al, 2005;Mevers et al, 2018;Perez et al, 2020). Greer et al (2016) evaluated three of those recommended treatment components with children of typical development in an early childhood education center, with treatment implemented by classroom teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Greer et al, however, did not include caregivers in this study. Although this study did not focus their evaluation of the effectiveness of the toilet training package on children with ASD or developmental disabilities (only one of the 19 participants had an ASD diagnosis), other researchers have explored toilet training interventions with children in these populations more thoroughly (e.g., LeBlanc et al, 2005;Mevers et al, 2018;Perez et al, 2020). Perez et al (2020) extended the toilet training package outlined by Greer et al (2016) to include children with ASD between the ages of two and 13.…”
Section: Introductionmentioning
confidence: 99%